2021
DOI: 10.1016/j.puhe.2021.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of severe symptomatic laboratory-confirmed SARS-CoV-2 reinfection

Abstract: Objective To evaluate factors predicting severe symptomatic laboratory-confirmed (reverse transcription-quantitative polymerase chain reaction, RT-qPCR) SARS-COV-2 (severe acute coronavirus-2) reinfection. Study design A nationwide retrospective cohort study was conducted in Mexico. Method Data from 258 reinfection cases (at least 28 days between both episodes onset) were analyzed. We used risk ratios (RR) and 95% confidence intervals (CI) to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 4 publications
4
33
0
Order By: Relevance
“…However, some studies reported that a small proportion (about 1%) of the population can be RP for SARS-CoV-2, and possibly due to reactivation or reinfection (16,17). Furthermore, previous reports (7,34,35) highlighted that RP-SARS-CoV-2 is less likely to cause serious problems to public health since the rate of RP seems low (about 1%), and new infections declining after recovery from the first episode of the infection (16,35), which is likely due to the suspected herd immunity (97,98). This suggests that previously infected individuals have a significantly lower risk of being infected for the second time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, some studies reported that a small proportion (about 1%) of the population can be RP for SARS-CoV-2, and possibly due to reactivation or reinfection (16,17). Furthermore, previous reports (7,34,35) highlighted that RP-SARS-CoV-2 is less likely to cause serious problems to public health since the rate of RP seems low (about 1%), and new infections declining after recovery from the first episode of the infection (16,35), which is likely due to the suspected herd immunity (97,98). This suggests that previously infected individuals have a significantly lower risk of being infected for the second time.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies (9)(10)(11), some COVID-19 patients were found positive from RT-PCR results for the second time (usually) within 5-13 days after discharge from the isolation before confirmation of reactivation or relapse (5,29,30), while some patients were found to be RP-SAR-CoV-2 at least 4 weeks from the first episode of the infection, indicating the possibility of reinfection (6,7). Therefore, urgent research is needed to disentangle possible reasons of RP-SAR-CoV-2 after recovery from primary infection to guide policy-making and help in controlling further spared of the virus (9,(31)(32)(33)(34).…”
Section: Standard Discharge Criteria For Sars-cov-2 Patientsmentioning
confidence: 91%
See 3 more Smart Citations